Pengaruh Perceived Manager Support, Employee Relation Climate, Dan Perceived Organizational Support Terhadap Kepuasan Kerja - Gunawan, Hikmad Tyar; Kurniawan, Ignatius Soni; Syawfan Lysander, Mohammad Ahyar (Universitas Islam Kadiri, 2025)
This study focuses on investigating whether perceived manager support, Employee relation climate, and perceived organizational support have a positive and significant impact on job satisfaction levels. The research sample was taken from the Dewapatih Tourism Organization at Goa Cemara, Bantul. A census method was employed for data collection. Data were obtained through a questionnaire distributed to 70 respondents via the information desk of the Dewapatih Tourism Organization, ensuring data collection quality. A total of 70 questionnaires were processed for data analysis. The data were analyzed using regression methods. The findings highlight that perceived manager support and Employee relation climate do not significantly impact job satisfaction. However, the study indicates that perceived organizational support has a positive and significant effect on job satisfaction. These findings emphasize the importance of implementing perceived organizational support to enhance employee job satisfaction effectively.